2005
DOI: 10.1007/s00383-005-1497-3
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of a prenatally detected large mullerian duct remnant

Abstract: Mullerian duct remnants presenting in childhood are often diagnosed incidentally and when symptomatic, typically present with recurrent infection and/or voiding disturbances. We present a rare unusual case of a male neonate who presented with a prenatally detected large pelvic cyst that turned out to be a giant prostatic utriculus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Surgical treatment should be reserved only for symptomatic utricle cysts. The definitive treatment of symptomatic utricular cyst is open excision or laparoscopic excision but endoscopic transurethral cyst drainage, cyst orifice dilatation, incision and deroofing have been described as well [10][11][12]. Our patient was treated endoscopically by cyst orifice incision and drainage with successful outcome.…”
Section: Discussionmentioning
confidence: 78%
“…Surgical treatment should be reserved only for symptomatic utricle cysts. The definitive treatment of symptomatic utricular cyst is open excision or laparoscopic excision but endoscopic transurethral cyst drainage, cyst orifice dilatation, incision and deroofing have been described as well [10][11][12]. Our patient was treated endoscopically by cyst orifice incision and drainage with successful outcome.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, to our knowledge, there are no reports of the outcome with these techniques in female infants with pelvic MDCs. Johal et al [8] reported a male neonate with MDC that was diagnosed during a routine prenatal sonographic examination. The mass was successfully removed via a Pfannenstiel laparotomy incision at 3 months of age.…”
Section: Discussionmentioning
confidence: 98%
“…The mass was successfully removed via a Pfannenstiel laparotomy incision at 3 months of age. However, the child developed postoperative voiding difficulty that was managed by a temporary vesicostomy [8].…”
Section: Discussionmentioning
confidence: 99%
“…This congenital anomaly is usually diagnosed in pediatric population [1,2] or in adults [3]. Acute urinary retention is not uncommon in the elderly and is mainly caused by prostatic diseases.…”
Section: Introductionmentioning
confidence: 99%